Eliciting Dual-Niche Immunological Priming by Acupoint Delivery of Nanovaccines - Wang, Lu; Sun, Yanhong; Yan, Meiling; Wang, Lihua; Wang, Yiyang; Zhang, Mengmeng; Li, Qian; Wu, Huangan; Liu, Jinyao; Fan, Chunhai (Nano-Micro Letters, 2025)
Immunization has long played essential roles in preventing diseases. However, the desire for precision delivery of vaccines to boost a robust immune response remains largely unmet. Here, we describe the use of acupoint delivery of nanovaccines (ADN) to elicit dual-niche immunological priming. ADN can simultaneously stimulate mast cell-assisted maturation of dendritic cells at the acupoint and enable direct delivery of nanovaccines into the draining lymph nodes. We demonstrate that ADN not only provokes antigen presentation by lymph node-resident CD8α+ dendritic cells, but also induces the accumulation of nanovaccines in B-cell zones, amplifying antigen-specific cytotoxic T lymphocyte responses and immunoglobulin G antibody expression in draining lymph nodes. ADN also generates systemic immune responses by causing immune memory and preventing T-cell anergy in the spleen. Further supported by evoking effective antitumor responses and high-level antiviral antibodies in mice, ADN provides a simple yet versatile platform for advanced nanovaccination. Highlights: 1 We report the use of acupoint delivery of nanovaccines (NVs) to elicit a dual-niche immunological priming by simultaneously stimulating mast cell-assisted maturation of CD11b+ dendritic cells (DCs) at the acupoint and directly enriching NVs into the draining lymph nodes (dLNs). 2 The dual-niche immunological priming not only provokes antigen presentation by LN-resident CD8α+ DCs, but also induces the accumulation of NVs in B-cell zones, highlights a facile yet versatile platform for advanced nanovaccination toward tumor therapy and infection prevention.